2005
DOI: 10.1111/j.1365-3024.2005.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear cell subsets in bronchoalveolar lavage fluid duringDictyocaulus viviparusinfection of calves: a potential role for γ/δ TCR‐expressing cells in airway immune responses?

Abstract: Mononuclear cell populations in the lungs of calves infected with Dictyocaulus viviparus were studied during primary infection and reinfection in order to identify cells involved in development of protective immunity to parasitic bronchitis. Three groups of calves were either inoculated with 500 third-stage larvae at both weeks 0 and 10 (n = 6), inoculated only at week 10 (n = 6), or remained uninfected (n = 3). The animals were monitored weekly by collection of bronchoalveolar lavage fluid (BALF), blood and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…The experiment was designed to compare cellular immune responses to D. viviparus in naïve and immune animals (approved by the Ethical Committee for Animal Experiments, Uppsala, Sweden, C26/3) and has been described in detail . In brief, three groups of 2‐ to 3‐month‐old calves were included in the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiment was designed to compare cellular immune responses to D. viviparus in naïve and immune animals (approved by the Ethical Committee for Animal Experiments, Uppsala, Sweden, C26/3) and has been described in detail . In brief, three groups of 2‐ to 3‐month‐old calves were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The inoculum contained 500 L3 larvae per animal of a D. viviparus isolate originating from Intervet, the Netherlands, and was given orally. Bronchoalveolar lavages were performed once per week on each calf, starting week ‐1 as described previously . The concentration of nucleated cells in the recovered BALF was determined by counting in Türks solution, and ≤ 6 × 10 6 BALF cells were collected for use in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parallel accumulation of γδ T lymphocytes and eosinophils in the tissue has also been demonstrated in another model of lung biased Th2 response: parasitic bronchitis triggered by the infection with Dictyocaulus viviparus (a bovine lung worm). Increased γδ T cell and eosinophil numbers were detected in the BAL fluid of infected calves, indicating the role of γδ T cells in the pathogenesis of D. viviparus -induced Th2 response and possible in eosinophil accumulation (Hagberg et al, 2005). An interesting piece of information that must be highlighted from this paper is that eosinophils recovered from BAL fluid of N .…”
Section: γδ T Lymphocytes In Allergymentioning
confidence: 99%
“…However, eosinophils isolated from calves do bind to the surface of D. viviparus in vitro and do inhibit their mobility (Knapp and Oakley 1981), which may suggest an effector role for eosinophils during disease. Hagberg et al (2005) have also reported that eosinophils in BAL peak 2 weeks after primary infection and again 2 weeks after secondary challenge (12 weeks after primary challenge), and this correlates strongly with peaks in γδ T cells in BAL. Furthermore, eosinophils and γδ T cells are found in greatest numbers compared with other granulocytes or lymphocytes in BAL from infected cattle.…”
Section: Cattle Lungwormmentioning
confidence: 77%